The mediating role of burnout syndrome between regulatory focus/motivation and intention to leave in teachers - Carlotto, Mary Sandra (2023)
Teachers are exposed to various occupational stressors which, if persistent, can lead to Burnout Syndrome and to recurrent thoughts of leaving the profession and culminate in total withdrawal. Thus, the objective of the present study was to evaluate the mediating role of Burnout Syndrome between the two dimensions motivational system that is constituted by the regulatory system with a focus on prevention and promotion and the Intention to Leave the profession among teachers in Southern Brazil. A total of 781 elementary school teachers from public and private schools participated in the research. The research instruments used included the Burnout Syndrome Questionnaire, the Regulatory Focus Scale, and a single item to evaluate the Intention to Leave the profession. The results obtained by Structural Equation Modeling confirmed the hypothesis that Burnout Syndrome plays a mediating role between promotion regulatory focus and the Intention to Leave the profession. The results reveal the importance of interventions that contemplate the reduction of occupational stressors for the prevention or rehabilitation of Burnout Syndrome in teachers.